THE INFLUENCE OF THE QUIZ TEAM LEARNING MODEL ASSISTED BY IT MEDIA AND LEARNING MOTIVATION ON SCIENCE LEARNING OUTCOMES AND SOCIAL SKILLS IN STUDENTS CLASS VI ELEMENTARY SCHOOL NO. 067097 MEDAN - Mahdalena; Hasruddin; Nur’aini (SENSEI RESEARCH CENTER, 2021)
This study aims to see the influence of Team Quiz and motivation on improving student learning outcomes and their effect on social skills. The type of this research is a quasi-experimental type with a 2-factor factorial design. The sample of this study was 50 people, consisting of 25 students in class VI-A, and 25 students in class VI-B. This study uses a questionnaire that previous experts have validated. The control and experimental classes were differentiated based on the motivational questionnaire pretest, and then the social skills questionnaire pretest was conducted. The success of the Team Quiz model can be concluded based on the posttest results, namely the success of students in learning outcomes by 28% and increasing students' social skills by 32%